HOW INSTITUTIONAL OWNERSHIP MODERATES ESG DISCLOSURE, FINANCIAL DISTRESS, AND RELATED PARTY TRANSACTIONS ON TAX AGGRESSIVENESS? - Nadya Mutiara Sari; Badingatus Solikhah (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study aims to analyze the effect of ESG disclosure, financial distress, and Related Party Transactions (RPT) on tax aggressiveness, as well as to examine the role of institutional ownership as a moderating variable. The research uses a quantitative method and covers 841 non-financial companies listed on the Indonesia Stock Exchange from 2020 to 2024. This yields 3,965 unbalanced panel observations obtained through purposive sampling, processed using winsorization to minimize outliers, and analyzed using multiple linear regression and moderated regression analysis. The results indicate that ESG disclosure, financial distress, RPT each have a positive and significant effect on tax aggressiveness. Institutional ownership weakens the influence of ESG disclosure and financial distress, but does not moderate RPT’s effect. Theoretically, these findings reinforce agency theory, highlighting the role of monitoring mechanisms in curbing opportunistic management behavior. The results also support legitimacy theory by illustrating how ESG practices may serve as image building tools, even when firms are incentivized toward aggressive tax behavior. The novelty of this study lies in positioning institutional ownership as a moderating governance mechanism and offering comprehensive evidence from multi-industry non-financial firms in Indonesia, thereby strengthening insights into how ESG disclosure, financial distress, and RPT shape corporate tax aggressiveness.